Avaliação de riscos em contratos de obras públicas utilizando o método fuzzy topsis - Sampaio, Andressa Dyalla de Sá (2023)
The construction industry faces considerable challenges due to the risks and uncertainties present in contracts, which can have serious financial, operational and reputational consequences. During the bidding and contracting phases, poor risk management results in delays in project execution, increased costs, litigation and legal disputes, as well as the delivery of poor-quality works and even the stoppage of public works. To ensure adequate risk management in public works contracts, it is essential to adopt efficient measures. This includes carrying out a thorough analysis of the contracts, identifying clauses and conditions that may generate risks or uncertainties. In addition, it is essential to establish a clear definition of responsibilities, ensuring that all parties involved are fully aware of their obligations and commitments. By adopting such measures, it is possible to mitigate the risks inherent in public works contracts, promoting more effective management and avoiding adverse consequences. In this way, projects can be carried out more efficiently, within the stipulated deadlines, within the expected budget and with the expected quality, providing benefits both for the parties involved and for society. In this context, this research aims to propose a decision support model for risk assessment in the contracting of public building works. Initially, a literature search was carried out to identify and merge the uncertainties related to the theme. Subsequently, the Fuzzy TOPSIS method was used to classify and select the major risks in contracts, considering the criteria of cost, time and quality, covering two types of works and considering the opinion of the decision makers. The results contribute to assist contracting parties in identifying and categorizing contractual risks, promoting a more effective management aligned with the interests involved.